Comparison of the Stability of Sandblasted, Large-Grit, and Acid-Etched Treated Mini-Screws With Two Different Surface Roughness Values: A Histomorphometric Study. Issue 1 (15th January 2022) - Seker, Elif Dilara; Yavuz, Ibrahim; Yucesoy, Turker; Cenkci, Ebru; Yay, Arzu
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose: To evaluate the effects of 2 different surface roughness values produced by sandblasted, large-grit, and acid-etched treatments at different loading conditions on the stability of mini-screws. Material and Methods: A total of 56 mini-screws (Group 1; 28 with Ra value of 1 μm, Group 2; 28 with Ra value of 1.5 μm) were inserted into the tibia of fourteen New Zealand rabbits. Surface analysis was performed before the placement of the miniscrews using multi-technique characterization. The mini-screws were loaded with 500 grf after different healing times: unloaded, immediate, 4 and 8 weeks. Resonance frequency analyses were performed immediately after mini-screw placement and at the end of loading. Biomechanical and histomorphometric analyses were also performed at the end of the loading period. Results: All mini-screws preserved their stability at the end of the loading period. However, the resonance frequency analyses showed higher implant stability quotient scores for 8-week group, unlike the immediate loading and unloaded groups ( P < 0.05). According to the infinite focus microscopy results, prolongation of healing time resulted in a greater bone area on the loaded mini-screws in Group 2 ( P < 0.05). Similarly, the histomorphometric analysis revealed higher bone-to-implant contact values in the 8-week group. There was no significant difference in the stability between the miniscrews with the Ra values of 1 and 1.5 μm. Conclusions: Sandblasted, large-grit, and acid-etched treated mini-screws showed significantly higher stability with healing time under heavy forces. Sandblasted, large-grit, and acid-etched treated mini-screws can be removed without fracture of the screw or the bone surfaces.